Strategic Planning Of Sytem And Information Technology Based On Ward And Peppard(Case Study : State Junior High School 1 Waru Sidoarjo) - Ronggo Alit; Mohammad Idhom (Prosiding International conference on Information Technology and Business (ICITB), 2017)
State Junior High School 1 Waru Sidoarjo has a great responsibility towards the development of a government-administered educational programs such as creating graduates who learned and believe. But at less utilization of  information technology is one of the factors is the maximum system working as well as the results achieved in the State Junior High School 1 Waru Sidoarjo. Ward and Peppard is a method of analysis that can assist in the strategic planning of isystems and nformation technology in order to maximize the achievement of vision and mission of the organization. Using analysis tools such as value chain, CSF (Critical Success Factor), PEST (Political, Economic, Social, Technology), five forces porter and McFarlan Strategic Grid can maximize the presence of application of information technology as one of the success factors in the achievement of the vision and mission of the organization. In this result produce recommendations for improvement that can maximize information technology as one of competitiveness with other competitors and quality improvement as technology progress. Keywords : Strategic Planning, Systems and Information Technology, Ward and Peppard